2016
DOI: 10.1038/ncomms11379
|View full text |Cite
|
Sign up to set email alerts
|

TRC8-dependent degradation of hepatitis C virus immature core protein regulates viral propagation and pathogenesis

Abstract: Signal-peptide peptidase (SPP) is an intramembrane protease that participates in the production of the mature core protein of hepatitis C virus (HCV). Here we show that SPP inhibition reduces the production of infectious HCV particles and pathogenesis. The immature core protein produced in SPP-knockout cells or by treatment with an SPP inhibitor is quickly degraded by the ubiquitin–proteasome pathway. Oral administration of the SPP inhibitor to transgenic mice expressing HCV core protein (CoreTg) reduces the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
81
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(84 citation statements)
references
References 59 publications
3
81
0
Order By: Relevance
“…Following cleavage, SP is retrotranslocated into the cytosol prior to nuclear entry and binding to viral RNA (27, 32). Membrane extraction of MMTV-encoded SP is independent of cleavage by SPP or SPP-like enzymes (29), unlike other viral and cellular signal peptides (3436). In this study, we used the UBAIT method to detect cellular proteins that associate with SP even transiently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following cleavage, SP is retrotranslocated into the cytosol prior to nuclear entry and binding to viral RNA (27, 32). Membrane extraction of MMTV-encoded SP is independent of cleavage by SPP or SPP-like enzymes (29), unlike other viral and cellular signal peptides (3436). In this study, we used the UBAIT method to detect cellular proteins that associate with SP even transiently.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Rem cleavage is required for SP function in this assay since mutations of the consensus signal peptidase recognition site prevent SP function and localization to the nucleolus (27, 29, 32, 33). SP release from microsomal membranes is independent of signal peptide peptidase (SPP) (29), which affects membrane release of some other viral signal peptides (3436). Our previous experiments have demonstrated that uncleaved Rem is stabilized by the presence of proteasomal inhibitors, whereas cleaved SP levels are similar in the presence and in the absence of proteasome inhibitors (27).…”
Section: Introductionmentioning
confidence: 99%
“…TRC8 binds heme oxygenase through the transmembrane region (32), and degradation is initiated by SPP cleavage in the transmembrane helix, similar to other tailanchored proteins (48). Hepatitis C virus core protein requires SPP cleavage to reach its mature form, and lack of SPP activity produces a short-lived immature form that is recognized by TRC8 (34). In these cases, the degraded proteins may be considered abnormal, and their clearance resembles protein quality control.…”
Section: Discussionmentioning
confidence: 99%
“…Second, SPP cleavage leading to TRC8 degradation requires a flexible luminal region unobstructed by glycosylation (48), whereas hERG only has short luminal loops between multiple transmembrane helices, and an N-linked glycosylation site (54). Third, all of the SPP-cleaved TRC8 substrates have single transmembrane helices so the cleaved products are released into the cytosol (33,34,48), and hERG is a tetramer of subunits with six transmembrane helices each.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that in vivo inhibition of SPP by using the GSI LY-411 575 (18, Fig. 5) leads to lower expression of hepatitis C virus core particles and improves liver function in a mouse model [92]. This suggests that SPP may be used as a future drug target for treatment of hepatitis C. However, selective inhibitors may be needed in order to minimize toxicity by c-secretase inhibition.…”
Section: Selectivity Of Inhibitorsmentioning
confidence: 99%